Posner's cluster revisited: Direct imaging of nucleation and growth of nanoscale calcium phosphate clusters at the calcite-water interface - Wang, L.; Li, S.; Ruiz-Agudo, E.; Putnis, Christine; Putnis, Andrew (2012)
Although many in vitro studies have looked at calcium phosphate (Ca-P) mineralization, they have not emphasized the earliest events and the pathway of crystallization from solvated ions to the final apatitic mineral phase. Only recently has it become possible to unravel experimentally the processes of Ca-P formation through a cluster-growth model. Here we use mineral replacement reactions by the interaction of phosphate-bearing solutions with calcite surfaces in a fluid cell of an atomic force microscope (AFM) and reveal that the mineral surface-induced formation of an apatitic phase proceeds through the nucleation and aggregation of nanosized clusters with dimensions similar to those of Posner's clusters, which subsequently form stable amorphous calcium phosphate (ACP) plates prior to the transformation to the final crystalline phase. Our direct AFM observations provide evidence for the existence of stable Posner's clusters even though no organic template is applied.